Health‐Related Quality of Life among Chronic Opioid Users, Nonchronic Opioid Users, and Nonopioid Users with Chronic Noncancer Pain. (25th February 2018) - Hayes, Corey J.; Li, Xiaocong; Li, Chenghui; Shah, Anuj; Kathe, Niranjan; Bhandari, Naleen Raj; Payakachat, Nalin
Abstract : Objective: Evaluate the association between opioid therapy and health‐related quality of life (HRQoL) in participants with chronic, noncancer pain (CNCP). Data Sources: Medical Expenditure Panel Survey Longitudinal, Medical Conditions, and Prescription Files. Study Design: Using a retrospective cohort study design, the Mental Health Component (MCS12) and Physical Health Component (PCS12) scores of the Short Form‐12 Version 2 were assessed to measure mental and physical HRQoL. Data Collection: Chronic, noncancer pain participants were classified as chronic, nonchronic, and nonopioid users. One‐to‐one propensity score matching was employed to match chronic opioid users to nonchronic opioid users plus nonchronic opioid users and chronic opioid users to nonopioid users. Principal Findings: A total of 5, 876 participants were identified. After matching, PCS12 was not significantly different between nonchronic versus nonopioid users (LSM Diff = −0.98, 95% CI: −2.07, 0.10), chronic versus nonopioid users (LSM Diff = −2.24, 95% CI: −4.58, 0.10), or chronic versus nonchronic opioid users (LSM Diff = −2.23, 95% CI: −4.53, 0.05). Similarly, MCS12 was not significantly different between nonchronic versus nonopioid users (LSM Diff = 0.76, 95% CI: −0.46, 1.98), chronic versus nonopioid users (LSM Diff = 1.08, 95% CI: −1.26, 3.42), or chronic versus nonchronic opioid users (LSM Diff = −0.57, 95% CI: −2.90, 1.77). Conclusions: Clinicians should evaluate opioid use in participants with CNCP as opioid use is not correlated with better HRQoL.